The Sabotage in The Election Campaign - Sulistyowati, Sulistyowati; Maharani, Dewi Nadya; Maharaja, Gusti Bintang; Manoppo, Hanifa Putri (Law Development Journal, 2024)
Campaign problems occur throughout the election from year to year, resulting in unrest in public opinion. Manipulation to sabotage is carried out to bring down legislative opponents of other candidate pairs that cause elections to occur haphazardly and override the correct campaigning provisions under the law. The emergence of sabotage carried out to seek the popular vote during the campaign casts doubt on the existence of clean and safe elections. Parties that should be considered neutral during the campaign until the election show their support for one of the competing legislative candidate pairs, which makes the neutrality of certain parties doubtful during the election. The occurrence of a haphazard campaign can damage the image of the election in the eyes of the public by realizing the view that campaigns and elections are meaningless as long as the ruling party uses its power to create a good image for one candidate as a competitor. Efforts to prevent dirty campaigns can be started by stopping sabotage carried out by supporters or candidates themselves to weaken opponents' voices armed with campaign Education and minimize the spread of false news during the campaign. Law enforcement should be maximized. The rules must be perfected.